The Influence of Online Games on Class V Students' Interest in Learning at SD Negeri 4 Banda Aceh - fatmawaty, dhea; Mislinawati, Mislinawati; Fauzi, Fauzi (Elementary Education Research, 2024)
This research aims to determine the effect of online games on the learning interest of class V students at SDN 4 Banda Aceh. This research uses quantitative research methods with associative research. This research was carried out at SDN 4 Banda Aceh with a sample size of 43 class V students at SDN 4 Banda Aceh. The data collection technique in this research provides questionnaires using a Likert scale to students. The data analysis technique uses a simple linear regression calculation formula. The test in this research uses SPSS 26. Furthermore, the regression used in this research is simple linear regression using 25 items in the questionnaire data, where the 25 items consist of 19 items of the Online Game variable (X) and 6 items of the Learning Interest variable. Student (Y), based on the results of tests carried out on the online game variable on the student interest variable, shows that online games have a significant effect on student interest in learning. This can be seen from the coefficient value which is positive, namely 0.890 and the sig value is 0.028 0, 05 so that H0 is rejected and H1 is accepted.